Pengaruh Pengembangan Kompetensi dan Karir terhadap Kinerja Karyawan di PT Mufida Fajar Utama - Anggito Dwi Romadhon (Al-Kharaj : Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2023)
This study aims is finding out the competency and career development affect the Performance of Employees at PT. MUFIDA FAJAR UTAMA, with a total of 50 employees. Researcher use a sampling technique using the Slovin technique which is based on the calculation of the sample who became respondents, a whole employees of PT. MUFIDA FAJAR UTAMA as many as 50 people. The method for collecting the data is using questionnaire. Regression with a significant level of 0.05 is used for technique analysis. The results of this study show that: (1) Competency development has a positive effect on the performance of PT. MUFIDA FAJAR UTAMA significantly. (2) Career development has a positive effect on the performance of employees of PT. MUFIDA FAJAR UTAMA significantly. (3) Competency and career development have a positive effect on the performance of employees of PT. MUFIDA FAJAR UTAMA significantly. Keywords: competency, career, employee performance